A study on the relationship between physical exercise and feelings of inferiority among college students: the chain mediating effect of social support and emotional regulation ability - Peng, Bo; Chen, Weisong; Wang, Hongshen; Yu, Ting; Kong, Mingmin (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore the impact of physical exercise on feelings of inferiority among college students, focusing on the mediating roles of social support and emotional regulation ability. The research investigates both direct and indirect pathways to understand how physical exercise enhances psychological resilience and mitigates negative self-perceptions.MethodsA sample of 2,036 college students from 15 provinces in China was surveyed using validated scales for physical exercise, feelings of inferiority, social support, and emotional regulation ability. Structural equation modeling (SEM) was employed to test hypothesized pathways, including direct effects and chain mediation effects. Gender invariance was assessed through multi-group analysis to ensure consistency across male and female participants.ResultsPhysical exercise significantly reduces feelings of inferiority, both directly and indirectly. Social support and emotional regulation ability independently mediate this relationship, with social support further enhancing emotional regulation in a sequential chain mediation effect. Gender invariance testing confirmed that these relationships are consistent for male and female students. Key findings indicate that physical exercise fosters social connections and strengthens emotional regulation, collectively promoting psychological resilience and reducing feelings of inferiority.ConclusionThe findings emphasize the critical role of physical exercise in enhancing mental health among college students through social and emotional pathways. Holistic intervention programs incorporating physical activities with social interaction and emotional skill-building can effectively alleviate feelings of inferiority. These insights provide actionable recommendations for educational institutions to promote mental health and foster inclusive, supportive campus environments.